The Effect of Manalagi Apple Juice (Malus Sylvestris Mill) on Stability and Antioxidant Activity of Black Tea - Fauziyah, Riska Salfa; Darmawati, Asri; Purwanto, Djoko Agus (Berkala Ilmiah Kimia Farmasi, 2022)
Black tea (Camellia sinensis O.K var assamica) is one of the most widely consumed beverages by the public. Antioxidant compounds that can counteract free radicals are contained in Manalagi apple (Malus sylvestris Mill) juice and black tea. The purpose of this study was to prove that an increase in antioxidant activity and stability of black tea would be achieved with the addition of Manalagi apple juice. The DPPH (2,2-diphenyl-1-picrylhydrazyl) method was used to determine their antioxidant activities in this study. Antioxidant activity was measured in black tea at 0, 6, and 24 hours after the addition of Manalagi apple juice. Antioxidant stability of black tea was compared to black tea added with Manalagi apple juice. The results obtained showed that higher antioxidant activity of a mixture of black tea and Manalagi apple juice was indicated than the antioxidant activity of black tea alone. It was shown that a lower IC50 of a mixture of black tea and Manalagi apple juice was obtained compared to black tea. An increase in the stability of the antioxidants in the black tea solution was also observed with the addition of Manalagi apple juice, and the slope of the linear equation % inhibition of the mixture was found to be lower by about one third than black tea. Because of this reason, a slowdown in the degradation rate of the antioxidant activity of black tea is achieved by adding Manalagi apple juice.Keywords: Black Tea, Manalagi Apple Juice, DPPH, Antioxidant